Neutralizing interferon‐α blocks inflammation‐mediated vascular injury via PI3K and AMPK in systemic lupus erythematosus. Issue 2 (20th June 2021) - Ding, Xuewei; Xiang, Wei; Yi, Ren; Huang, Xiaoyan; Lin, Qiuyu; He, Xiaojie
Abstract: Plasmacytoid dendritic cells (pDCs) play a key role in the initiation and amplification of systemic lupus erythematosus (SLE)‐associated vascular injury. In this study, we found that dsDNA induced dose‐ and time‐dependent increase in IFN‐α and Toll‐like receptor 7 (TLR7), TLR9 and IRF7 expression in pDCs. Co‐cultured circulating endothelial cells (ECs) with activated pDCs significantly decreased proliferation, tube formation and migration in ECs. The elevated level of cellular IFN‐α increased cell adhesion, promoted cell apoptosis, induced cell senescence and arrested cells at G0/G1 phase of endothelial progenitor cells (EPCs). Additionally, the co‐culture system activated MAPK and inactivated PI3K. Pristane was used to establish a in vivo SLE‐like mouse model. Importantly, we showed that INF‐α‐neutralizing antibody (IFN‐α‐NA) rescued all the changes induced by IFN‐α in vitro and prevented vascular injury in pristane‐induced SLE model in vivo . In conclusion, we confirmed that activated pDCs promoted vascular damage and the dysfunction of ECs/EPCs via IFN‐α production. IFN‐α‐neutralizing antibody may be a clinical implication for preventing vascular injury. PI3K signalling and AMPK signalling were associated with SLE‐associated vascular functions. Abstract : Pristane can cause obvious damage to the blood vessels of ApoE−/− mice, the pathological morphology of the arterial tissue of the SLE mouse model is disordered, and the basement membrane is thickened. The treatment of IFN‐α‐NA reverses these phenotypes. The expression of IFN‐α receptor in the vascular endothelium is increased, and that of SA‐β‐Gal‐positive EPCs in vascular endothelium is enhanced.